2013
DOI: 10.5144/0256-4947.2013.241
|View full text |Cite
|
Sign up to set email alerts
|

The burden of Rotavirus gastroenteritis among hospitalized pediatric patients in a tertiary referral hospital in Jeddah

Abstract: BACKGROUND AND OBJECTIVESTo evaluate the burden of Rotavirus gastroenteritis (GE) among pediatric hospital admissions.DESIGN AND SETTINGSThis is a retrospective observational study, in which all pediatric cases admitted to one of the biggest tertiary hospitals in Jeddah, with the diagnosis of GE, in the year 2010, were enrolled.PATIENTS AND METHODSThis is a retrospective observational study in which all pediatric cases admitted with the diagnosis of GE in the year 2010 were enrolled. Clinical data and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In Saudi Arabia Rotarix® vaccine coverage rate increased from 84% in 2013–94% in 2014, since vaccine introduction in January 2013 [WHO, ]. In this study, the observed overall RVA infection rate of 9.2% during the 2‐year post‐vaccination period is lower than that reported in previous Saudi studies, which found values ranging from 12% to 46% before vaccine introduction [Kheyami et al, ; Kheyami, ; Afifi and Nabih, ; Aly et al, ]. Moreover, the percentage of RVA as the etiological agent of AG decreased from 11.3% in the first year of the study to 6.8% in the second year (39.8% reduction in the average percentage of RVA‐positive cases), strongly suggesting that vaccination caused this marked decrease in RVA disease burden.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In Saudi Arabia Rotarix® vaccine coverage rate increased from 84% in 2013–94% in 2014, since vaccine introduction in January 2013 [WHO, ]. In this study, the observed overall RVA infection rate of 9.2% during the 2‐year post‐vaccination period is lower than that reported in previous Saudi studies, which found values ranging from 12% to 46% before vaccine introduction [Kheyami et al, ; Kheyami, ; Afifi and Nabih, ; Aly et al, ]. Moreover, the percentage of RVA as the etiological agent of AG decreased from 11.3% in the first year of the study to 6.8% in the second year (39.8% reduction in the average percentage of RVA‐positive cases), strongly suggesting that vaccination caused this marked decrease in RVA disease burden.…”
Section: Discussioncontrasting
confidence: 65%
“…Therefore, continuous surveillance studies in the post‐vaccination period are crucial in order to collect epidemiological data on vaccine impact on RVA genetics, identify the effects of the vaccine program on circulating strains, particularly on dominant genotypes and the emergence of unusual strains, and identify possible uncommon events and genetic diversity between vaccine and circulating strains [Steyer et al, ; Velasquez et al, ; Bucardo and Nordgren, ]. In Saudi Arabia, previous studies have investigated the prevalence of RVA‐AG and epidemiological patterns of RVA genotypes in different regions during the pre‐vaccination era and data after Rotarix® introduction in the NIP are completely absent [Kheyami, ; Afifi and Nabih, ; Aly et al, ]. Therefore, this, we believe, the first study to investigate the prevalence of RVA‐AG and the distribution of the RVA genotypes as well as to determine a possible change in the age of occurrence of the RVA infection in the first 2 years after the vaccine introduction in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 14 , 15 However, to date, no national studies have been conducted. Recent studies in the country have indicated that RVGE remains the most common cause of infectious diarrhea in young children, 16 , 17 but the prevalence of RV may have decreased. 18 , 19 Although effective control of RVGE relies upon knowledge of national disease burden data and the prevalent circulating strains of RV, more data need to be collected for Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Mendalawi. 1 Our study recommendation stated, “In view of the high disease prevalence among children, locally and worldwide, and in view of the effectiveness of vaccination shown in the previous studies and our study, we recommend routine Rotavirus vaccination as the most effective available means of control despite improvement in sanitation and hygiene. Surveillance for the efficacy and effectiveness of vaccination as well as the differential efficacy of the 2 available vaccines is recommended.” We hope that with the current vaccination program, the prevalence of RPG will dramatically decrease, and we plan to have further studies to assess the efficacy of vaccination in our community.…”
mentioning
confidence: 80%